EXPLORATION AND MORPHOLOGICAL CHARACTERIZATION OF THE SUGAR PALM (Arenga pinnata Merr.) IN SIKAKAP, MENTAWAI ISLANDS - Nike Karjunita; Dede Suhendra; Wulan Kumala Sari; Sri Heriza (BPFP Universitas Bengkulu, 2025)
Sugar palm (Arenga pinnata), a member of the Arecaceae (Palmae) family within the Angiospermae group, is a multifunctional plant with significant economic value. Its sap serves as a primary ingredient for palm sugar production, while its young fruit is consumed as food, its fibers are utilized for roofing, and its trunk is processed into handicrafts. However, concerns have arisen regarding the plant’s declining availability due to imbalanced cultivation. A key factor contributing to the low cultivation interest among farmers is the prolonged maturation period of sugar palm. To support conservation efforts and sustainable management, morphological characterization is crucial in determining genetic relationships, which can assist breeders in preserving germplasm stability. This study aimed to assess the morphological characteristics and genetic diversity of sugar palm populations in Sikakap District, Mentawai Islands. The research was conducted from August to November 2024 using a survey method with purposive sampling. Morphological data were collected through direct observation, analyzed descriptively, and similarity relationships were determined using NTSYS Ver. 2.10 software. The exploration identified 15 accessions categorized into two groups, with genetic similarity levels ranging from 27% to 50%. A similarity coefficient of 27% indicates significant morphological variation among the observed accessions, particularly in plant height, sheath length, stem circumference, number of leaflets, leaflet width, leaflet length, and fruit diameter. The accession Pagai Selatan (PS2) exhibited the greatest morphological divergence. These findings provide valuable insights for conservation strategies and selective breeding programs aimed at maintaining the genetic diversity and sustainability of sugar palm populations.